Listeria monocytogenes meningitis in an immunocompetent adult: a case report - Zhang,Yi (2012)
Listeria monocytogenes (L. monocytogenes) is an uncommon cause of bacterial meningitis in immunocompetent adults. Patients with immunosuppression are at increased risk of developing serious invasive diseases, particularly meningitis. We describe a case of meningitis caused by L. monocytogenes in an immunocompetent and previously healthy 34-year-old adult. The patient received treatment with intravenous ampicillin plus amikacin and made a full recovery. L. monocytogenes should be suspected in immunocompetent adults with bacterial meningitis who fail to respond to empirical antibiotic treatment.